Developing Vendor Evaluation Model for Third-Party Manufacturing: Vendor Management System in SMEs Fashion Industries - Darayani Darayani; Yuliani Dwi Lestari Lestari (Green Publisher Indonesia, 2026)
Outsourcing is extensively adopted by fashion SMEs, with many SMEs experiencing problems with such activities, such as high defect rates, inconsistent delivery, poor communication, and low bargaining power. These problems often arise due to the fact that vendor evaluation is informal and has no clear criteria. This study develops a vendor evaluation model using the Analytic Hierarchy Process (AHP) to assist SMEs in making more structured decisions. The research comprised three phases: validation of vendor selection criteria based on the BCOR framework, inputs from nine fashion business owners via a structured questionnaire, and calculation of criteria weights with AHP for two groups of SMEs. Since the patterns of judgment between the two groups were similar, a single weighting model was created. A numerical example of three vendors and a sensitivity analysis were then performed. Results show that Cost and Risk are the most important criteria, with production cost, risk of inconsistency in quality, and vendor reputation being important subcriteria. The model proved to be very stable and can help SMEs to evaluate vendors more objectively.